The Use of Bali Cattle on Local Feed Resources for Beef Cows Development in Indonesia - Kusuma Diwyanto; Atien Priyanti (Indonesian Center for Animal Research and Development, 2008)
Bali cattle as an animal genetic resource of Indonesia is one of the appropriate cattle breed to be developed in Indonesia. Intensification of breeding program using Bali cattle may solve one of the heifer supply shortage in the beef cattle industry. Technology innovation base on the local feed resources and the use of agricultural by products is needed to meet the demand of sustainable feed supply for beef cattle. This will be the main basic components on the complete feed formulation that is cheap and easily accessible for the farmers. The crop livestock systems innovation through the zero waste approach need to be implemented to yield the zero cost cattle raising system. The cow calf operation system will only be run sustainable if the feed cost and the use of external inputs can be minimized. The program need to be integrated by the grower and fattening (finisher) activities. The grower cattle activities, such as run by the Center Village Cooperation in East Nusa Tenggara could afford the farmers participation and had a significant contribution to the farmers’ household. The success of an introduction program is largely determined by the involvement of the farmers in the very beginning based on the local indigenous technology. There is a need to empower the farmers group based on the cooperative principles to increase bargaining power, information accessibility and communication effectiveness. This effort will also simultaneously conducted with the policy support on accessibility of micro finance through the agriculture credit scheme. Key words: Bali cattle, local feed, beef cattle business